Evolution of Subduction Cusps From the Perspective of Trench Migration and Slab Morphology - Hui Zhao (Frontiers Media S.A., 2021)
The geometries of trenches vary worldwide due to continuous plate boundary reorganization. When two trenches intersect to generate a corner, a subduction cusp is formed. Although subduction cusps are frequently observed throughout historical plate movement reconstructions, few studies have been conducted to explore the controlling factors of trench migration and slab morphology along subduction cusps. Here, we use a 3-D dynamic subduction model to explore the influence of the overriding plate strength, initial slab-pull force, and initial cusp angle on the evolution of subduction cusps. Our numerical model results suggest the following: 1) subduction cusps have a tendency to become smooth and disappear during the subduction process; 2) the slab dip angle is smallest in the diagonal direction of the subduction cusp, and a larger cuspate corner angle leads to a larger slab dip angle; 3) the asymmetric distribution of the overriding plate strength and initial slab-pull force determine the asymmetric evolutionary pathway of subduction cusps. Our results provide new insights for reconstructing the evolution of subduction cusps from seismological and geological observations.